The effect of risedronate on orthodontic tooth movement in ovariectomized rats. (September 2019) - Wu, Dongle; Meng, Bowen; Cheng, Yangfan; Gan, Lei; Huang, Peina; Cao, Yang
Highlights: Risedronate inhibits orthodontic tooth movement in ovariectomized rats. Risedronate reduces TRAP-positive cells on the pressure side of the tooth. Risedronate may function by regulating the RANK/RANK ligand/osteoprotegerin pathway. Abstract: Objective: This study aimed to investigate the effect of risedronate on orthodontic tooth movement in ovariectomized rats. Methods: Forty-five female Sprague-Dawley rats were divided into three groups. Bilateral ovariectomies were performed on the rats in the ovariectomy and ovariectomy + risedronate groups. Two weeks after ovariectomy, risedronate was administered intraperitoneally every three days in the ovariectomy + risedronate group, while rats in the ovariectomy and sham groups were administered saline until they were sacrificed. One month after ovariectomy, nickel-titanium alloy closed-coil springs were placed between the maxillary left first molar and the maxillary left incisor. On days 3, 7 and 14, five rats from each group were sacrificed. The distance of orthodontic tooth movement was measured by a digital caliper, and slides were obtained for histological analysis. Results: The distance of orthodontic tooth movement and the number of tartar-resistant acid phosphatase (TRAP)-positive cells were the highest in the ovariectomy group, followed by those in the ovariectomy + risedronate group, on days 3, 7 and 14. The positive expression levels of receptor activator of nuclear factor-kappa β (RANK) ligand and cathepsin K were the strongest while the positive expression of osteoprotegerin in the ovariectomy group was the weakest, followed by the corresponding expression levels in the ovariectomy + risedronate group, on days 3, 7 and 14. Conclusions: Risedronate can inhibit orthodontic tooth movement in ovariectomized rats and may function by regulating the RANK/RANK ligand/osteoprotegerin pathway.